FORMA CZYNNOŚCI PRAWNEJ W PRAWIE PRYWATNYM MIĘDZYNARODOWYM - Pazdan, Jadwiga (Zeszyty Prawnicze, 2017)
Form of Legal Act in Private International Law Summary The form of a legal act in private international law is usually governed by particular conflict rules. Such provisions define the scope of their application. The aim of conflict rules is to indicate territorial application of different legal systems. That function fixes the approach while determining the way of understanding the notion of a „form” in private international law. The appropriate approach is the autonomic qualification. That is why I admit that the form in private international law is nothing else that the way of submission and incorporation of the declaration of will, being a component of a legal act. According to art. 12 of Polish Act on private international law from 1965 (1965 Act), the form of a legal act is governed by the law proper for that act (the first rule), however, it is sufficient to fulfill the conditions of the law of the country where the legal act is undertaken (the second rule). Lex causa, relevant to the form of a legal act (art. 12 section 1 of 1965 Act), may be indicated not only by means of conflict rules based on objective factors of alien, but also by the choice-of-law clause (if a choice of law is not forbidden). Nevertheless, a choice of law regarding solely the form of a legal act is not acceptable. The choice of law for the form of a legal act cannot be justified by the permissibility of a partial choice of law, which is supposed to be a choice relative to that part of legis causae, which is taken into consideration while determining the conditions required for the form of a particular legal act, on the base of art. 12 section 1 1965 Act. Although, there is no fragment of the legis causae applied in the scope of the form, there is complete lex causae or divided into segments (in the case of a complex or simple choice of law). The form cannot constitute such a segment. It has its own status. The second rule is subsidiary to the first one. The mutual relation of these two rules has subsequent consequences: 1 lex loci actus may be applied only when the conditions of lex causae were not fulfilled; 2 the answer to the question if the legis loci actus constitutes the proper law for the form of a legal act is dependent on the fact whether during the performance of the legal act the requirements resulting from that law were fulfilled; 3 when the conditions regulated by both lex causae as well as lex loci actus were not fulfilled, it is to lex causae to decide about the consequences (sanctions) of non-fulfillment of the requirements relating to the form; 4 lex loci actus cannot be replaced by the Polish law by the virtue of art. 7 of 1965 Act, when the content of the law binding on the territory where the legal action was undertaken cannot be determined; 5 the transmission and remission, based on the conflict rules binding in that country where the legal act was undertaken, is not allowed; 6 the requirements of legis loci actus are also fulfilled when there are no special requirements relating to the form. The legal act will be valid in such a situation although the requirements relating to the form, resulting of lex causae, were not fulfilled. The place where the legal act is performed understood as the factor of alien in art. 12 section 2 of 1965 Act must be interpreted in the light of autonomic qualification. The decisive role should be granted to the place where an event which brought (or should have brought) to the performance of a legal act had happened while the contractual relation has been formed. De lege ferenda, I am opting for the maintenance of both rules in Polish law, however, their position should be equal. In case of discrepancy of the effects the preference should be granted to those more favorable for the legal act (the solution in favorem negotii).